IMPROVING THE QUALITY OF TRANSPORT LOGISTICS SERVICES ON REGIONAL AND INTERNATIONAL ROUTES - Bobonazarova, Jamila; Akhmedov , Zokhid (Science technology&Digital finance, 2024)
This article explores the importance of the development of transport logistics services by connecting the Republic of Uzbekistan to International Transport Highways, ensuring the independence of our country’s transport and diversifying Foreign Relations. Recommendations have been made to improve the types of clustering in the use of competitive advantages of a particular area by dividing common resources in the supply of national products by interdependent activities, simplifying the application of innovative technologies, attracting tangible and intangible assets, reducing transactional costs.